Economic Analysis of the Operation of a Hydropower Plant in a Wastewater Treatment Plant: Toruń, Poland - Paweł Tomczyk; Krzysztof Mastalerek; Karol Kociszewski; Wojciech Orzepowski; Mirosław Wiatkowski (Energies)
The energy industry is constantly changing and evolving. One of the visible solutions is the pursuit of low-emission solutions. One such solution is investment in renewable energy sources (RESs), including hydropower, which in 2023 will constitute a dominant share in the production of electricity from RESs (47.02%) in the world. One of the alternative solutions is the use of hydropower in wastewater treatment plants, whose global potential is estimated at about 4350 TWh. An important issue in the operation of these facilities is their profitability. This article presents an economic analysis of a hydropower plant in the wastewater treatment plant in Toruń (northern Poland) in order to assess its profitability in the context of profits, costs, and payback period. The analyses showed the profitability of 9 out of 12 characterized variants, with the payback period estimated for real variants at 10.75–23.74 years and for theoretical variants at 5.06–5.32 years. The most significant factor in reducing the payback period was the level of electricity production between years, while different types of settlements and changes in electricity sales prices played a lesser role. Taking into account all profitable variants, after 25 years of operation, the net income will amount to PLN 1.07 million for the actual variants and PLN 3.18 million for the theoretical variants. The work can contribute to understanding the specifics of the operation of such facilities, which is consistent with, among others, the goals of sustainable development, climate and energy policies, or the circular economy.